1988
DOI: 10.1364/ao.27.000790
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity function as a design tool for high focal depth

Abstract: The optical transfer functions for variable focus error are contained as a single picture representation in the ambiguity function that is associated with the pupil function. This picture representation is shown to be useful for designing pupil functions that increase the depth of focus. We specify a criterion for an optical transfer function with low sensitivity defocus in terms of a nonlinear differential equation for the point spread function. Based on this approach, we design and compare five new spatial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Later on, we explored the use of the ambiguity function for shaping the OTF [29][30][31]. For the sake of completeness of our presentation, we discuss out-of-focus image formation when using a classical, 4-f, optical processor, as the one in Fig.…”
Section: Anamorphic Processors and The Ambiguity Functionmentioning
confidence: 99%
“…Later on, we explored the use of the ambiguity function for shaping the OTF [29][30][31]. For the sake of completeness of our presentation, we discuss out-of-focus image formation when using a classical, 4-f, optical processor, as the one in Fig.…”
Section: Anamorphic Processors and The Ambiguity Functionmentioning
confidence: 99%
“…This novel approach was later applied for expanding the OTF vs. focus errors as a Taylor series expansion 11 . It was found that half of the terms (of the Taylor series) can be reduced to zero if the complex amplitude transmittance of the pupil aperture is a hermitian function.…”
Section: Introductionmentioning
confidence: 99%
“…In optics, the WDF has been introduced by Bastiaans 16 and the most common optical set up used to display it has been implemented by Bartelt, et al 17 for the 1-D and 2-D spatial functions. A hybrid processor for image processing has been proposed by Gonzalo, et al 18 Other applications in optics can be found in the analysis of complex amplitude pupil functions 19 and in the explanation of paraxial polychromatic optics 20 . In most of the WDF applications implicitly are involved the linear, paraxial and isoplanatic conditions, and the mathematical properties of this function can be found in the classical paper of Claasen and Mecklenbräuker 21 .…”
Section: Introductionmentioning
confidence: 99%